ANALISIS DAMPAK PELAKSANAAN FUNGSI PERENCANAAN DAN PENGAWASAN BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI IKIP PGRI MADIUN - M.Th. Kuswariningsih (Universitas PGRI Madiun, 2013)
Students evidently often lose sight of the essence of planning and controlling on learning practice, in spite of knowing that they are influential against their learning achievement. This research serves a thorough out-look on tbe impact of planning and controlling functions on learning practice carried out by the students of Department of Economy Teaching, IKIP PGRI MADIUN. The subjects of this research are students of Department of Economy Teaching, IKIP PGRI MADIUN, with 50 of whom have been chosen to be the sample. The method of the research is co relational descriptive study posing the relationship among variables. The data are drawn by means of questionnaire and documentation. The data analysis is carried out to have r-test, F-test and t-test aided with SPSS for Windows V L6.0. The analysis shows tbat there is significant influence of planning and controlling oftbe learning practice against the students achievement, which is proven by l